Biochemical and Ultrastructure Changes in the Kidney of Streptozotocin-Induced Diabetic Rat - Al-Kushi, Abdullah G. (Pakistan Journal of Nutrition, 2013)
Diabetes mellitus alters the cellular production of eicosanoids in a number of tissues, including the kidney and these agents have in true been implicated in the pathogenesis of diabetic nephropathy. The aim of this work was to study the effect of streptozotocin-induced diabetes on a kidney by light and electron microscopy. Twenty four adult male white albino rats were collected and classified into 2 main groups. The first (treated) group by a single Streptozotocin (STZ) injection (60 mg/kg) intra-peritoneal (i.p). The second group was considered control. The blood samples were collected for Fasting Blood Sugar (FBS), cholesterol, creatinine and triglycerides The survival rate in diabetic rats was 66.6% in contrast to 100% in controls. There was a significant weight loss (p = 0.01) in diabetic rats while a highly significant weight gain (p = 0.002) was recorded in control ones. The kidney weight in diabetic rats showed an extremely significant increase (p = <0.004). The rats injected with STZ have shown severe hyperglycaemia (p<0.0001). Serum cholesterol showed a highly significant rise in both diabetic (p = 0.007) and control rats (p = 0.001). Both creatinine values (p<0.0001) and serum triglycerides (p = 0.0004) were significantly higher in diabetic rats than in control rats. The kidney of induced diabetic rats showed a Histopathological and ultrastructure changes in both kidney. In conclusion, STZ-induced diabetes mellitus had deleterious effects in both structure and function of the rat kidney. Intensive management of diabetes mellitus in human is recommended to delay or prevent such diabetic nephropathy.